2019
DOI: 10.3310/eme06110
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine to increase live births in euthyroid women with thyroid antibodies trying to conceive: the TABLET RCT

Abstract: Background Thyroid autoantibodies, specifically thyroid peroxidase antibodies, have been associated with miscarriage and pre-term birth in women with a normal thyroid function. Small randomised controlled trials have found that treatment with levothyroxine may reduce such adverse outcomes in pregnancy. Objectives The Thyroid AntiBodies and LEvoThyroxine (TABLET) trial was conducted to explore the effects of levothyroxine in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…This large, multicenter, prospective RCT concluded that for the 540 participants who became pregnant during the study, levothyroxine at a dose of 50 µg started prior to pregnancy and continued to the end of the pregnancy was of no benefit in increasing the proportion who attained a live birth at or beyond 34 completed weeks' gestation. 10 The T4Lifetrial, another multicenter, prospective RCT, examined the effect of levothyroxine treatment in 187 euthyroid pregnant women with TPO-Ab positivity and a history of recurrent pregnancy loss. Compared with placebo, levothyroxine treatment did not result in higher live birth rates (defined as birth of a living fetus > 24 weeks' gestation).…”
Section: Thyroid Autoantibodies and Miscarriagementioning
confidence: 99%
See 2 more Smart Citations
“…This large, multicenter, prospective RCT concluded that for the 540 participants who became pregnant during the study, levothyroxine at a dose of 50 µg started prior to pregnancy and continued to the end of the pregnancy was of no benefit in increasing the proportion who attained a live birth at or beyond 34 completed weeks' gestation. 10 The T4Lifetrial, another multicenter, prospective RCT, examined the effect of levothyroxine treatment in 187 euthyroid pregnant women with TPO-Ab positivity and a history of recurrent pregnancy loss. Compared with placebo, levothyroxine treatment did not result in higher live birth rates (defined as birth of a living fetus > 24 weeks' gestation).…”
Section: Thyroid Autoantibodies and Miscarriagementioning
confidence: 99%
“…11 Findings from both the TABLET study and the T4Lifetrial support that the use of levothyroxine is not beneficial to prevent miscarriage in women with recurrent pregnancy loss who are euthyroid and positive for TPO-Ab. 10,11 The 2017 ATA guidelines provide evidence-based recommendations for clinicians caring for pregnant women with thyroid conditions. The guidelines note that there is not enough evidence to convincingly determine a beneficial impact of levothyroxine administration on the reduction of pregnancy loss in newly pregnant TPO-Ab-positive euthyroid women with a history of pregnancy loss.…”
Section: Thyroid Autoantibodies and Miscarriagementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is increasing data regarding the association of thyroid dysfunction and thyroid autoimmunity with adverse pregnancy outcomes such as miscarriage, recurrent embryo implantation failure and preterm delivery [28,47,[71][72][73][74][75][76]. The higher risk of miscarriage could have multiple causes, including a relative thyroid hormone shortage, caused by a decreased thyroid functional capacity, an impaired thyroid response to human chorionic gonadotropin, or a higher general susceptibility to autoimmunity [77][78][79][80].…”
Section: Effects On Fertility Pregnancy and Fetal/newborn Outcomesmentioning
confidence: 99%
“…Nevertheless, studies evaluating treatment with levothyroxine to euthyroid RPL patients positive for TPO antibodies do not find an improved pregnancy outcome [195,197,198]. TPO antibody positivity is associated with an increased risk of (subclinical) hypothyroidism in pregnancy [196].…”
Section: Hypothyroidismmentioning
confidence: 99%